MAP selection algorithms based on future movement prediction capability in synthetic and realistic environment - Vilhar, Andrej (Array, 2008)
Abstract: Efficient mobility management involves micro-mobility principles. The performance of the Hierarchical Mobile IPv6 (HMIPv6) protocol, a representative micro-mobility approach, is affected by the Mobility Anchor Point (MAP) selection. In this paper, we propose a new selection method based on a prediction of the future movements of Mobile Nodes (MNs). The proposed algorithms exploit the information about the future availability of MAPs and choose those MAPs that assure a better service. An improvement to the evaluation methodology is also proposed. The algorithms are compared to each other not only in synthetic but also in realistic internet topologies, which has not been a practice in the past. The simulation results show promising improvements in terms of distance from chosen MAPs and frequency of MAP changes. Moreover, we showed that, for perceivable improvement of MAP selection, absolute accuracy of movement prediction is not required. As pioneers in the mobility management analysis in realistic environment, we ascertain that offering MAP services over more than one Autonomous System (AS) proves beneficial